Answering big questions with small data: the use of field experiments in primate cognition - Benítez, Marcela E; Painter, Melissa C; Guisneuf, Nicole; Bergman, Thore J (Current opinion in behavioral sciences, 2022)
Understanding how animals navigate the information landscape is challenging in the wild. Field experiments are a powerful approach to understanding information use and, consequently, cognition in natural settings. Here, we review three types of experiments used to study primate cognition in the wild: 1) presentation experiments that manipulate the availability of information, 2) presentation experiments that manipulate the coherence of information, and 3) interactive experiments that allow subjects to generate new information. Together these approaches have uncovered a rich but varied cognitive world in primates. Going forward, we see these successes continuing to grow as cognitive experiments can be combined with biologging and large behavioral data sets, automated to increase sample sizes, and combined with physiological measures. •Wild primates use a range of information to optimize their behavior.•Field experiments can help unpack how wild animals navigate the information landscape.•We review two types of field experiments: presentation and interactive paradigms.•Future opportunities include incorporating big data, physiology, and automation.